Analisis Kritis: Impelentasi Projek Penguatan Profil Pelajar Pancasila (P5) pada Pendidikan Anak Usia Dini - Wulan Tini (Institut Madani Nusantara, 2024)
The implementation of the Pancasila Student Profile Strengthening Project (P5) at the Early Childhood Education (PAUD) level within the Independent Curriculum was originally designed to foster children's character through a liberating approach. However, in practice, this paradigm shift has created epistemological and methodological conflicts for teachers in the field. This study aims to conduct a critical analysis of the implementation of P5 at the PAUD level, with a specific focus on pedagogical readiness, structural workload, and teachers' stuttering in translating the abstract values of Pancasila into child-friendly stimulation. Using a qualitative approach with critical case studies, data were collected from several PAUD units through in-depth interviews with teachers, participatory observation of the project process, and critical analysis of teaching module documents compiled independently by teachers. The results reveal the phenomenon of